The Use of Application Anyflipas Media Storytelling in Early Childhood - Riyadi, Agung Afif; Rabbani, Adinda Zakiah; Dewi, Nurul Fitria Kumala (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to examine the effectiveness of the AnyFlip application as a digital storytelling medium in improving early childhood language skills. The research method uses a quantitative experimental approach with a Pre-experimental One-Group Pretest-Posttest Design involving early childhood children at TK Aisyah Bustanul Athfal through purposive sampling technique. The study was conducted in three sessions with a duration of 30 minutes per session in experimental and control classes. The experimental class applied the storytelling method using the AnyFlip application that facilitates interactive learning through visual and audio features, while the control class used conventional methods. The research instrument was a performance test to measure speaking ability and story retelling. Data were analyzed using paired sample t-test after meeting the normality and homogeneity prerequisite tests. The results showed a significant difference with the experimental class average of 80.70 and control class of 67.50. A significance value of less than 0.05 indicates that the AnyFlip application has a positive effect on improving early childhood language skills. The study concludes that integrating AnyFlip with storytelling methods is effective in developing children's expressive language skills in the digital era.